On the craft of writing (Journal of Parents and Teachers, 1997)
Language is presented as a gift and an essential tool to express emotions, memories and sounds in a unique way. The community of 400 million Spanish speakers is highlighted, as well as Nebrija's contribution in 1492 by creating the first grammar to unify the language in the peninsula. Communication is compared to the art of painting and music.
Keywords: language; spanish speakers; grammar; communication